Digital Image Processing An Algorithmic Introduction Using Java - Burger, Wilhelm; Burge, Mark J. (Texts in Computer Science, 2008)
"This will be one of my continuing reference books for some time to come." Steve Cunningham, PhD, Past President of SIGGRAPH "An excellent resource for the users of ImageJ." Wayne Rasband, author of ImageJ This modern, self-contained, textbook explains the fundamental algorithms of digital image processing through practical examples and complete Java implementations. Available for the first time in English, Digital Image Processing is the definitive textbook for students, researchers, and professionals in search of critical analysis and modern implementations of the most important algorithms in the field. • Practical examples and carefully constructed chapter-ending exercises drawn from the authors' years of experience teaching this material • Real implementations, concise mathematical notation, and precise algorithmic descriptions designed for programmers and practitioners • Easily adaptable Java code and completely worked out examples for easy inclusion in existing, and rapid prototyping of new, applications • Self-contained chapters and additional online material suitable for a flexible one- or two- semester course • Uses ImageJ, the image processing system developed, maintained, and freely distributed by the U.S. National Institutes of Health (NIH) • A comprehensive Website (www.imagingbook.com) with complete Java source code, test images, and additional instructor materials This comprehensive, reader-friendly introduction is ideal for foundation courses as well as eminently suitable for self-study. Wilhelm Burger is the director of the Digital Media degree programs at the Upper Austria University of Applied Sciences at Hagenberg. Mark J. Burge is a program director at the National Science Foundation (NSF) and a principal at Noblis (Mitretek) in Washington, D.C.